Ladies in stripes: taxonomic confusion in a potential mimicry complex among Wallacean Coccinellidae (Coleoptera: Coccinellidae) - Li, Jiahui; Tomaszewska, Wioletta; Pang, Hong; Ślipiński, Adam (Zootaxa, 2014)
Two species of ladybird beetles, one belonging to Phrynocaria Timberlake (Coccinellni) and the second to Chilocorus Leach (Chilocorini) collected by R.A. Wallace in the Maluku Islands (Indonesia) have identical body size and colour pattern with longitudinal stripes on elytra. Their external features were so similar that G.R. Crotch included both of them in the type series of Chilocorus wallacii Crotch, 1874. The specimen designated as the lectotype of Chilocorus wallacii belongs to Phrynocaria. Coelophora wallacii Crotch, 1874 is also transferred to Phrynocaria (new comb.) and becomes senior homonym and Phrynocaria crotchi new name is proposed for the secondary junior homonym. Chilocorus crotchi sp. nov. is described for the taxon misidentified as Chilocorus wallacii Crotch.